Advances in knowledge discovery and data mining - Fayyad, Usama M...[et al.] eds (American Association for Artificial Intelligence / Massachusetts Institute of Technology Menlo ParkUS, 1996)
Examines and describes techniques and tools for transforming data into useful knowledge. Deals with fundamental issues of discovery; examines specific techniques for data mining including clustering and classification; presents methods for dealing with trend and deviation analysis; focuses on data mining techniques for deriving dependencies; and discusses integrated discovery systems. Presents approaches for next-generation database systems; and several real and successful applications.